PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN BANK UMUM SYARIAH DI INDONESIA - Fierda Shofa; Fuad Fuad (Diponegoro Journal of Accounting, 2014)
The purpose of this study was to determine the effect of intellectual capital on the financial performance of Islamic banks in Indonesia. Dependent variable used in this study is the financial performance of Islamic banks based on ROE, CTA and islamicity financial performance index. Independent variables used in this study is the intellectual capital which is measured by using Pulic model that called Value Added Intellectual Coefficient (VAIC) which has been modified by Ulum.The sample in this study is Islamic banking which is the Sharia Commercial Banks registered in Bank Indonesia in 2009-2013. The sample was selected using purposive sampling method. Study sample consisted of annual report from 11 Islamic banks in Indonesia. Total sample used 34 banks. Data analysis technique by Simple Linear Regression.The results showed that the intellectual capital significantly effect on ROE and CTA. Intellectual capital not an impact Islamicity financial performance (ZPR, PSR and Islamic Income vs Non Islamic Income)